Handbook on Experimental Economics and the Environment 2013
DOI: 10.4337/9781781009079.00011
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral foundations of environmental economics and valuation

Abstract: IntroductionFor at least 60 years, economists have worked on empirical approaches to measuring the value of non-market goods and services. In its beginnings, this research employed models of revealed preferences, such as the travel cost approach for recreation 1 or the hedonic property value model for air pollution. 2 Economists pursued valuation based on revealed preferences because they were initially interested in what now, from our vantage, appears to be a narrow range of nonmarket services-those services … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…The NOAA panel (Arrow et al 1993) recommended WTP estimation. However, with advances since then-both in our understanding of why WTP and WTA might diverge (Brown and Gregory 1999;Horowitz, McConnell, and Murphy 2013;Ericson and Fuster 2014;Kim et al 2015) and in the design of SP methods-this recommendation need not always hold. In cases where payment reductions are institutionally feasible and incentive-compatible questions can be designed, 36 WTA estimation may be practical and appropriate.…”
Section: Willingness To Pay Versus Willingness To Acceptmentioning
confidence: 99%
“…The NOAA panel (Arrow et al 1993) recommended WTP estimation. However, with advances since then-both in our understanding of why WTP and WTA might diverge (Brown and Gregory 1999;Horowitz, McConnell, and Murphy 2013;Ericson and Fuster 2014;Kim et al 2015) and in the design of SP methods-this recommendation need not always hold. In cases where payment reductions are institutionally feasible and incentive-compatible questions can be designed, 36 WTA estimation may be practical and appropriate.…”
Section: Willingness To Pay Versus Willingness To Acceptmentioning
confidence: 99%
“…Despite the popularity of intention data, there is considerable evidence that inconsistencies often exist between what people say they will do and what they actually do (Ajzen, Brown, and Carvajal, 2004;Horowitz, McConnell, and Murphy, 2008;Murphy and Stevens, 2004). This is generally attributed to hypothetical bias, which is defined as the difference between stated and observed actions (Horowitz et al, 2008). However, there is very little research that examines if this hypothetical bias influences people differently (Murphy and Stevens, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The last decade has witnessed a huge increase in popularity of behavioural economics (BE) (see Camerer et al, 2011, for a review) and, in turn, of its influences in environmental economics (e.g. Horowitz et al, 2008;Shogren and Taylor, 2008;Brown and Hagen, 2010). Experimental research in this area has repeatedly identified empirical phenomena that are not adequately explained by traditional neoclassical economic analysis.…”
Section: Insights From Behavioural Economicsmentioning
confidence: 99%